Gram Negative Bacterial Blood Stream Infections with Focus on Carbapenem Resistance: An Experience at a South Indian Tertiary Care Hospital - Prasanna N Bhat; Ganesh Nayak S; Anup Kumar Shetty; Kavitha Prabhu (Online Journal of Health & Allied Sciences)
Aims & Background: There is a lack of studies which determine the clinical outcomes and the characteristics of Gram-negative bacterial bloodstream infections (GNBSI) from India. In this retrospective study, we determine the risk factors for mortality in patients admitted at a tertiary care hospital with GNBSIs with focus on carbapenem resistant GNBSIs. Materials and Methods: A total of 375 patients admitted to the hospital from August 2020 to May 2022, with monomicrobial GNBSI were included in the study. The baseline characteristics of the patients were compared based on the carbapenem susceptibility of the pathogen. The independent risk factors for mortality were assessed at 7 days and 30 days since the GNBSI episode by Cox proportional hazards model. A sub-analysis was also performed in the subset of patients with event of intensive care unit (ICU) admission during the hospital stay. Results: Carbapenem resistant GNBSIs were detected in 36.53% (137/375) patients. Overall crude in-hospital mortality rate was 40.8% (153/375) among patients. The most common pathogens isolated were Escherichia coli (28.0%,105/375), Klebsiella pneumoniae (26.7%,100/375) and Acinetobacter species (17.3%, 65/375). Conclusion: Use of immunosuppressive drugs, ICU admission and need for vasopressors were independent risk factors for mortality. Among the 232 patients with ICU admission, carbapenem resistant Acinetobacter GNBSIs (CRA-GNBSIs) and Carbapenem resistant Klebsiella pneumoniae GNBSIs (CRKP-GNBSIs) were independent risk factors for mortality. There is a need for monitoring the carbapenem resistance and measures need to be taken to reduce it. Similarly, measures also need to be taken for early identification and effective treatment of GNBSIs to facilitate better outcomes.